Analysing 157 learning designs using learning analytic approaches as a means to evaluate the impact of pedagogical decision making. (23rd February 2016) - Toetenel, Lisette; Rienties, Bart
Abstract: Educators need to change their practice to adapt to a shifting educational context. By visualising learning design decisions, this article highlights the need to capture educators' "tacit" knowledge relating to course material, activity types and workload, through employing learning analytics methods in order to analyse the learning designs of courses taken by 60, 000+ students, common pedagogical patterns are identified. When analysing 157 learning designs using a taxonomy of seven different learning activities, we found that the majority of educators used two types of learning activities most widely, namely assimilative activities (reading, watching videos and listening to audio) and assessment activities. Surprisingly, educators do not choose different activity types based upon function (eg, replace one type of student‐activating activity by another), but patterns can be seen where educators combine assimilative, productive and assessment activities or assimilative, finding and handling information and communication tasks. While educators rely heavily on assimilative and assessment activities, no positive correlation was found between any of the seven learning design activity types and student outcomes. Our initial findings suggest that student outcomes are negatively correlated with a high proportion of assimilative activities. Further studies are needed to establish whether particular learning design decisions are related to student outcomes and whether these findings can be replicated in different research settings.